PEMBENTUKAN UNDANG-UNDANG CIPTA KERJA DENGAN METODE OMNIBUS LAW DITINJAU DARI PROSEDUR PEMBENTUKAN UNDANG-UNDANG - Doni Herlambang Nanda Kuswoyo (2021)
The aim of this research is to know the concept of law making process with the omnibus law method in terms of the Indonesian regulation system, also to know the process of making the Job Creation Law in the method of omnibus law in accordance of law making procedure, in this case, The Law Nr. 12 of 2011 concerning Formulation of Laws and Regulations. This research is using normative legal method with statute approach which uses secondary data in the form of primary, secondary and tertiary legal materials. The result of this research indicates the omnibus law making process results as the legal product which has not regulated neither in its form, material contained, drafting technique and stages of its formation. Moreover, the Job Creation Law with the omnibus law method is not in the accordance with the law making procedure in Indonesia. Therefore, it is necessary to revise the provision regarding the law making process in Indonesia in order to regulate the omnibus law method so that it can obtain firm and certain legal basis..